Improving Efficiency of Urea Fertilizers by Inhibition of Soil Urease Activity - Kiss, S.; Simih?ian, M. (Springer Netherlands, 2002)
The purpose of our present work is to review the fundamental studies on inhibition of soil urease activity and the applied studies on improving efficiency of urea fertilizers by inhibition of soil urease activity. The general literature on these topics covers 65 years, and the patent literature comprises a period of nearly 40 years. Studies related to inhibition of soil urease activity were performed in a great number of countries' well representing all the continents. Full texts of the papers describing these studies were published in one of 18 languages'. The literature data reviewed are structured into 10 chapters, 81 subchapters, and 224 sections. The bibliographical list consists of 830 papers cited. In alphabetical order: Argentina, Armenia, Australia, Austria, Belgium, Belorussia, Brazil. Bulgaria, Canada, China, Costa Rica, Cuba. Czech RepUblic, Egypt, Estonia, France, Georgia (Gruzia), Germany, Hungary, India, Iraq, Ireland, Israel, Italy. Japan, Kazakhstan, Lithuania, Malaysia, Moldova, Netherlands, New Zealand, Pakistan, Philippines, Poland, Romania, Russia, Saudi Arabia, Slovakia, South Africa, South Korea, Spain, Sri Lanka. Sudan, Sweden, Thailand, Turkey, Ukraine, United Kingdom, United States of America. Uzbekistan